Acknowledge, repeat, rephrase, elaborate: Witnesses can help each other remember more. Issue 5 (27th May 2016) - Vredeveldt, Annelies; Hildebrandt, Alieke; van Koppen, Peter J.
Abstract : Crimes are often observed by multiple witnesses. Research shows that witnesses can contaminate each other's memory, but potential benefits of co-witness discussion have not yet been investigated. We examined whether witnesses can help each other remember, or prune each other's errors. In a research design with high ecological validity, attendees of a theatre play were interviewed approximately one week later about a violent scene in the play. The couples that signed up for our study had known each other for 31 years on average. Participants were first interviewed individually and then took part in a collaborative interview. We also included a control condition in which participants took part in two individual interviews. Collaboration did not help witnesses to remember more about the scene, but collaborative pairs made significantly fewer errors than nominal pairs. Further, quantitative and qualitative analyses of retrieval strategies during the discussion revealed that couples who actively acknowledged, repeated, rephrased, and elaborated upon each other's statements remembered significantly more information overall. Taken together, our findings suggest that, under certain circumstances, discussion between witnesses is not such a bad idea after all.